Optimalisasi Pengalaman Ruang Pada Perancangan Stasiun Kereta Api Kota Lhokseumawe - Ade Andini; Erna Muliana; Hendra A (Universitas Syiah Kuala, 2022)
The increase in the number of train passengers continues to increase every year, so the development of station services must continue to be carried out in order to realize quality, fast, easy, affordable and measurable public services. Station planning and design are still focused on functional aspects, whereas psychological aspects also affect human perception of space. That is, the human need for space is more than just a physical aspect. As a result, boredom arises because of the lack of emotional expression or value as a characteristic of the station, this causes a lack of interaction between humans and space. Space experience can be achieved with multisensory abilities in humans. The variables that make up the experience of space include point, line, plane, color, texture, light, sound, smell, scale and proportion. A person's emotional state and the time of interaction also affect the resulting impression of space. After conducting an analysis to determine the impression of the desired space specifically, several space programs emerged, including family blocks, visitor galleries, food courts and music stages. By applying the appropriate spatial experience-forming variables, it will produce a maximum space experience and not be limited to the station.